2019
DOI: 10.31616/asj.2018.0121
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Factors Associated with Severe Pain in Post-Anesthesia Care Unit after Thoracolumbar Spine Surgery: A Retrospective Case-Control Study

Abstract: Study Design A retrospective case-control study. Purpose To evaluate the effect of nitrous oxide and anesthetic and operative factors associated with severe pain in the early postoperative period after thoracolumbar spine surgery. Overview of Literature Thoracolumbar spine surgery is the most common procedure in spine surgery, and up to 50% of the patients suffer from moderate to severe pain. Nitrous oxide has analgesic, anxiolytic, and anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A study that evaluated predictive factors of perioperative outcomes in patients undergoing thoracolumbar spine surgery found that higher preoperative ODI scores were predictive of higher VAS pain scores. This relationship was noted for a variety of spinal pathologies including failed back surgery syndrome, spinal stenosis, and spondylolisthesis [ 17 ]. The greater postoperative pain may be due to patients with higher disability catastrophizing their perceived pain.…”
Section: Discussionmentioning
confidence: 99%
“…A study that evaluated predictive factors of perioperative outcomes in patients undergoing thoracolumbar spine surgery found that higher preoperative ODI scores were predictive of higher VAS pain scores. This relationship was noted for a variety of spinal pathologies including failed back surgery syndrome, spinal stenosis, and spondylolisthesis [ 17 ]. The greater postoperative pain may be due to patients with higher disability catastrophizing their perceived pain.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, Tania casino et al and other study showed that less POP incidence with our result. 8,9 The differences were due to the timing of the pain assessment and the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Four articles discussed the criteria for discharge from the PACU (Hawker et al, 2017;Phillips et al, 2013Phillips et al, , 2014Revell et al, 2019). Other papers were assessments for a specific indicator, such as respiration (Shannon et al, 2020), pain (Kiavar et al, 2016;Rungwattanakit et al, 2019), neurologic assessment (Hall & Stanley, 2019;Herrero et al, 2017), delirium (Bishara et al, 2022;Huang et al, 2020), nausea and vomiting (Grass & Bundy, 2021), thirst (Wu et al, 2021) and temperature (Liu et al, 2023). There are three expert opinions on the components of nurses' comprehensive assessment in monitoring patients in anaesthesia recovery period (Brent, 2010;Kaplow, 2010;Street et al, 2018).…”
Section: Preliminary Construction Of the Nursing Assessment Framework...mentioning
confidence: 99%